Uforanderligt passioneret - Mørch, Michael Agerbo (Dansk Teologisk Tidsskrift, 2018)
The notion of God as immutable has received severe critique during the last centuries. Critics claim that this doctrine is an import from Greek metaphysics which is alien to the portrait of the biblical God as passionate and relational. In this article, I describe how it remains possible to talk about God as immutable, even after this critique, if we carefully define what is meant by the terminology. I suggest that God is ontologically immutable, but relationally mutable according to his genuine relationship with his creatures. What is always realized in the immanent trinity may take different shapes in the economy as the relationships develop. God has, therefore, different “modes of passion” suitable for every occasion. I conceptualize this understanding in the term “immutably passionate”.